The Interrelationship between Quality Costs and Pricing Decision-Making: An Exploratory Study on a Sample of Industrial Companies - Mohammed Hazim Issmeil Al-Ghazali (Journal of Information Technology Management)
There is a causal relationship between high-quality cost systems and pricing decision makers because pricing decision is in dire need of modern systems that help make rational decisions. The aim of this research is to confirm that quality cost systems affect pricing decisions-making in maintaining the industrial companies. The research results can be utilized by beneficiaries taking into account the effects, obligations and costs involved. This study focused on the importance of the growing interest of companies and individuals interested in quality on the necessity of maintaining the product quality and reaching the high quality of products through strategic decisions-making for the continuity of industrial companies and elimination of future risks. The problem of this study is that quality cost systems are among the most important factors involved in pricing decisions-making of industrial companies. This is attributed to the superiority of foreign companies' interest in high quality production over Arab companies in terms of their interest in product quality in pricing decisions-making within advanced methods used by these companies in maintaining the quality of their products. This study is based on the descriptive approach to form the theoretical base of research by relying on the relevant published books and scientific research. The analytical approach was then adopted through the questionnaire. Among the most important findings is the existence of a positive relationship between quality costs and pricing decisions. Hence, quality costs positively affect the rationalization of pricing decision by providing the necessary data and information about the risk to the organization in increasing the competitive advantage among companies. This competitive increase has led to an increase in seeking more opportunities for companies with quality costs. One of the most important recommendations is to prepare plans to mitigate the competitive risks that have been chosen. The aim of these plans is to provide the necessary information to make strategic long-term decisions, aiming at protecting the rights and interests of shareholders to economic unity and strategic decisions-making that serve interests.